DETERMINAN SURPLUS UNDERWRITING DANA TABARRU’ PADA PT PRUDENTIAL SHARIA LIFE ASSURANCE PERIODE 2016-2021 - Safitri, Dita Indah; Kornitasari, Yenny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research is motivated by the many cases of conventional insurance defaults, which have contributed to instilling a negative stigma against sharia insurance. In fact, in the process, Islamic insurance uses underwriting management of tabarru funds in its operational procedures to minimize default. By using Prudential Syariah as a research object for the 2016-2021 period, this study aims to determine the determinants of the underwriting surplus of tabarru funds. The research utilizes a quantitative approach with multiple linear regression analysis models using a purposive sampling method. The results of the study reveal: (i) the underwriting surplus of tabarru' funds is negatively and significantly affected by the net contribution; (ii) the underwriting surplus of tabarru' funds is negatively and significantly affected by claims expenses; (iii) the underwriting surplus of tabarru' funds is positively and significantly influenced by investment returns; (iv) the underwriting surplus of tabarru' funds was negatively and significantly affected by the BI-7 Day-RR. Through these results, Prudential Syariah is expected to maintain the stability of the underwriting surplus of tabarru' funds through suitable investment by considering the influence factors. The acceptance process also needs to be more selective to minimize risks so that defaults can be avoided in the future. This research may contribute to being a reference for decision-making regarding the underwriting surplus of tabarru funds and add concerns related to underwriting management.